THE NEED TO DEVELOP LEARNING MANAGEMENT IN THE COST MANAGEMENT IN FOOD BUSINESS COURSE FOR WORK-INTEGRATED LEARNING EDUCATION - Chinchoo, Sasathorn; Kanta, Sasipha (Journal of Education and Innovation, 2025)
Due to the ongoing economic slowdown, Thailand has established a framework to develop a key mechanism: humans, to become lifelong learners and self-developers. The food industry is one of the businesses that generate income for the country. Developing a workforce in this industry to be prepared and able to manage costs will help the country reduce its dependence on foreign experts. Students in Work-Integrated Learning (WIL) education are trained to practice in real workplaces alongside theoretical learning in classrooms. This research aimed to assess the needs and prioritize the development of learning management in the Cost Management in Food Business course for Work-Integrated Learning education. The sample for this research consists of 132 second and third-year undergraduate students from the Faculty of Food Business Management at Panyapiwat Institute of Management, selected using cluster random sampling. The research instrument for data collection is a needs assessment form for developing learning management in the Cost Management in Food Business course, which is in the form of a dual-response format between the current and expected conditions, using a 5-level rating scale. Data analysis was performed using the Priority Needs Index (PNI modified). The results showed that the need for learning management methods (PNI modified = 0.41) is the highest priority, followed by the learners’ needs (PNI modified = 0.40). These results allow instructors to prioritize which urgent matters are important in improving learning management and should they should be addressed first and to design appropriate learning processes for students in the future.